Delayed Onset of Bilateral Acute Retinal Necrosis Syndrome: A 46-Year Interval. (March 2015) - La Cava, Maurizio; Abbouda, Alessandro; Restivo, Lucia; Zito, Roberta
Abstract Background: Acute retinal necrosis (ARN) syndrome is an uncommon, severe form of retinitis that is caused by the herpes virus family. Bilateral acute retinal necrosis (BARN) at delayed onset is rare. Methods: A retrospective, interventional case is described in a 64-year-old man complaining of blurred vision in the left eye. The patient had a history of presumed ARN in the right eye at the age of 18 years. Results: The reduced visual acuity and the ocular fundus signs lead us to the diagnosis of delayed-onset BARN. Intravenous and intravitreal antiviral therapy, corticosteroid and antiplatelet treatment were administered until recovering final visual acuity. Conclusions: This report represents the longest reported interval of ARN quiescence with eventual bilateral involvement and illustrates the importance of long-term patient follow-up in immunocompetent patients.